Sales management for startups and SMEs - Hirst, Anderson (Abingdon, Oxon ; New York, NY : Routledge, 2025)
"Managers and entrepreneurs know they have a great product or service-but they may not know how best to sell it. Useful for nearly any sector or industry, this book is a thoroughly practical guide on how to build an excellent sales organisation, brick by brick. Creating an effective sales organisation is a challenge for many businesses, and it's easy to waste resources on ineffective approaches. Many MBA and executive education programmes do not cover sales management in any depth. Filling this knowledge gap, this guide will help readers to create their own unique high-performing sales organisation that fits their product and market environment. Evidence-based and field-tested, it will gives answers to critical questions, including: Which sales process should we use? How do we recruit, retain, and inspire our sales team? What should we measure and how should we manage it? What do great sales managers do? Rich with case studies from the author's 25 years of sales consulting experience, this book will appeal to a wide variety of managers and entrepreneurs who wrestle with the question "How do I grow my business?", from sales directors to startup founders to MBA students"--
Keywords: Sales management; Small business -- Growth; New business enterprises -- Management; BUSINESS & ECONOMICS / Sales & Selling; BUSINESS & ECONOMICS / Small Business